Peran Bahasa Indonesia Dalam Pengembangan Keterampilan Komunikasi Anak Pendidikan Anak Usia Dini - Maria Feronika Simatupang; Rawaty O F Panggabean; Nover Bintang Siahaan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Abstract Indonesian has an important role in developing children's communication skills at the early childhood education stage. This article discusses how the use of Indonesian can influence the development of children's communication skills at an early age, as well as effective methods for developing these skills. This research aims to explore the role of Indonesian in developing children's communication skills in Early Childhood Education (PAUD). This research uses qualitative methods by means of observation and interviews. Indonesian is not only a means of communication, but also a means of developing PAUD children's thinking, self-expression and social interaction skills. This article provides a deeper understanding of the role of Indonesian in developing children's communication skills at this stage of education. Apart from that, language development strategies in early childhood and effective communication models for developing creative thinking abilities are also discussed in this journal. Storytelling and role-play learning methods can also be used to develop children's language skills at an early age. It is important to pay attention to the role of Indonesian in early childhood education to improve their communication skills. By paying attention to the role of language, it can be easier to develop an effective and holistic learning approach in developing children's communication skills from an early age. The results of the research are that providing an understanding of Indonesian can play a role in developing communication skills in early childhood.